Analisis Pengaruh Kepuasan (Satisfaction), Kepercayaan (Trust) Dan Kemudahan Penggunaan (Perceived Ease Of Use) Terhadap Loyalitas Pelanggan Pengguna E-Commerce Tokopedia Di Surabaya - Reva Namira Salsabila; Budi Prabowo (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This research aims to analyze the variables of the influence of satisfaction (Satisfaction), trust (trust) and ease of use (perceived ease of use) on customer loyalty, on this occasion researchers use e commerce Tokopedia and its customers. The population used in this study is all users of tokopedia websites or applications in Indonesia. Given the large number of users of tokopedia websites or applications, researchers took samples from the population to be respondents in the study. Samples of this study were collected from customers who use Tokopedia's website or application and are domiciled in Surabaya. The samples in this study used probability sampling techniques. The type of probability sampling used is a simple random sampling method. The implications of the study focus on the real function of the results of the study to provide additional references in establishing the role of customer satisfaction towards loyalty on Tokopedia website.